Upgrading English Language Proficiency and Providing Optimum Nursing Care for Cardiac Patients: Perceptions of Non-native Nurses - Wannas, Amr Selim; Hassan, Inas Hussein (Magister Kajian Bahasa Inggris (English Language Studies) Universitas Sanata Dharma Yogy, 2023)
Linguistic competence and effective communication are essential for providing optimum care for patients. Cardiac care is among the high-alert settings that require highly proficient nurses to be attentive and provide the best possible care for patients with heart problems. This research aims to measure the perceptions of non-native nurses towards the correlation between upgrading their English language proficiency level and providing optimum nursing care for cardiac patients. To this end, a mixed-method research design, qualitative and quantitative, was adopted in the study. First, a questionnaire was constructed and disseminated to 210 Egyptian nurses working at the Magdi Yacoub Foundation (MYF) in Aswan, Egypt. Yet, 127 nurses responded to the questionnaire. Secondly, to ensure the reliability of the research results, observation and interviews with a selected number of questionnaire takers were used as data collection instruments. Findings revealed that upgrading the English language proficiency level is believed to contribute to enhancing the performance of cardiac care nurses, their professionalism, and their learning autonomy. In addition, a taxonomy of the nurses’ uses of English for Specific Purposes has been constructed during the study. The proposed taxonomy was constructed from the data from the questionnaire, the interview, and the observation. It can be used to identify nurses’ needs when designing English-for-nurses courses. It is recommended that further research is conducted to investigate the correlation between the level of English language proficiency and the performance of nurses in other medical sub-domains.